The impact of first trimester fasting glucose level on adverse perinatal outcome. (May 2018) - Salman, Lina; Arbib, Nissim; Borovich, Adi; Shmueli, Anat; Chen, Rony; Wiznitzer, Arnon; Hadar, Eran
Abstract Objective To evaluate the impact of first trimester fasting glucose (FTFG) level on perinatal outcome. Study design A retrospective cohort study of singleton deliveries. Maternal and neonatal outcome were compared between two groups—women with FTFG < 95 mg/dl and FTFG ≥ 95 mg/dl. Women with pre-gestational diabetes were excluded. Results Five thousand and thirty women met inclusion criteria. Of whom, 4644 (92.3%) had FTFG < 95 mg/dl and 386 (7.7%) had FTFG ≥ 95 mg/dl. Women with FTFG ≥ 95 mg/dl had higher rates of gestational hypertension (2.33 vs. 0.7%) and gestational diabetes (9.07 vs. 2.86%), p  < 0.05 for both. Moreover, they had higher rates of cesarean delivery and arrest of descent, p  < 0.05. Composite diabetes outcome was significantly higher among women with FTFG ≥ 95 mg/dl (8 vs. 3%, p  = 0.002). After adjusting for potential confounders, composite diabetes outcome (aOR = 1.942 95% CI 1.265–2.981, p  = 0.002) and gestational hypertension (aOR = 2.827 95% CI 1.295–6.175, p  = 0.009) remained significantly higher in the FTFG ≥ 95 mg/dl group. Conclusion FTFG ≥ 95 mg/dl is an independent risk factor for adverse perinatal outcome including gestational hypertension and diabetes-related complications.